2004
DOI: 10.1002/dc.20032
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic washing cytology in serous borderline tumors of the ovary using ThinPrep®: Are there cytologic clues to detecting tumor cells?

Abstract: The detection of tumor cells in pelvic washings of patients with serous borderline tumors of the ovary (SBT) remains a diagnostic challenge. Accurate diagnosis of pelvic washings is important in determining therapeutic regimens and assessing patient prognosis. No study has exclusively examined pelvic washing cytology of patients with SBT using only ThinPrep methodology. The purpose of this study is to examine whether cytologic clues exist in detecting tumor cells of SBT in pelvic washings processed with ThinPr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…C-1C). 21,25 In PW, SBT can be distinguished from reactive mesothelial cells by presence of two-cell population, absent intracellular windows, and the neoplas-tic features described above and distinguished from serous ca due to more prominent psammoma bodies. 25 A diagnosis of metastatic malignancy or mesothelioma in effusion requires confirmatory IC.…”
Section: Fig C-1 Amentioning
confidence: 99%
See 2 more Smart Citations
“…C-1C). 21,25 In PW, SBT can be distinguished from reactive mesothelial cells by presence of two-cell population, absent intracellular windows, and the neoplas-tic features described above and distinguished from serous ca due to more prominent psammoma bodies. 25 A diagnosis of metastatic malignancy or mesothelioma in effusion requires confirmatory IC.…”
Section: Fig C-1 Amentioning
confidence: 99%
“…21,25 In PW, SBT can be distinguished from reactive mesothelial cells by presence of two-cell population, absent intracellular windows, and the neoplas-tic features described above and distinguished from serous ca due to more prominent psammoma bodies. 25 A diagnosis of metastatic malignancy or mesothelioma in effusion requires confirmatory IC. Use of LBP in effusion cytology have shown to be less time-consuming with a low falsenegative rate (FNR) and high diagnostic sensitivity (99%) for malignant and suspicious fluids compared with other preparatory techniques.…”
Section: Fig C-1 Amentioning
confidence: 99%
See 1 more Smart Citation
“…Most authors recommend caution in overinterpreting psammoma bodies because they can be seen in pelvic washes from endometriosis, endosalpingiosis, and other nonmalignant pelvic diseases. 5,18,19 Covell maintains that psammoma bodies are of no diagnostic significance. 4 However, in a recent study of pelvic-washing cytology in BSTO using liquid-based preparation, psammoma bodies were the only statistically significant feature distinguishing BSTO from serous carcinoma, being more common in the former.…”
Section: Psammoma Bodiesmentioning
confidence: 99%
“…11 In another study, psammoma bodies in peritoneal washings were found to be the only statistically significant feature distinguishing serous borderline tumor from serous carcinoma, being more common in the former. 20 However, in order to qualify for a diagnosis of psammocarcinoma one needs to document innumerable psammoma bodies and a relative dearth of epithelial cells. According to Chen, the diagnosis of psammocarcinoma can only be suggested by cytologic features alone, as the presence or absence of an invasive pattern cannot be assessed in the cytologic specimens.…”
mentioning
confidence: 99%